Influence of Urban Land Markets on Emerging City Form;A Case of Dodoma National Capital City in Tanzania. - Azor William Nyakamwe; John Modestus Lupala; Emmanuel Elifadhili Mchome (African Journal on Land Policy and Geospatial Sciences, 2022)
Presently, one of the major challenges confronting the growth of rapidly urbanizing cities is the fact that, cities are growing in unsustainable form which is largely market-led growth and suffers from informal land market distortions. From a conventional point of view, planning aims at achieving compact growth. Presently, the pervasive knowledge gap especially inadequacies in theoretical premises on city forms and inadequate polices have contributed to mixed forms in many cities of the urbanizing world.  Extensive literature expounding on practical problems related to ineffective planning interventions is also scanty. This paper attempts to address the problems in the Tanzanian city context. It drew empirical evidences from four (4) settlements located in broad acre policy areas in Dodoma National Capital City.  Data were collected using official and household interviews, focus group discussions, measurements and observations. The study findings reveal that informal land buying and selling, informal plot subdivision and densification, informal change of land uses and unregulated land prices have contributed to the consolidated city form on areas closer to public services and Central Business District (CBD). The findings further reveal that there is sprawling of the city form in areas located far from public services, infrastructure and CBD. As a way forward it is recommended that, there is a need to revisit policies, legislation and guidelines governing city planning; agglomerate settlement centres and provide the same with services and infrastructure. It is also recommended that there is a need to redevelop areas along main roads and identify areas for infill development and establish special guidelines advocating towards compact city development